Analisis Kepatuhan Makan OAT pada Penderita Tuberkulosa Paru di Puskesmas Karya Mukti Kabupaten OKU - Darneli; Chairil Chairil; Ali Harokan (Jurnal Kesehatan Saelmakers PERDANA, 2023)
Pulmonary tuberculosis is a disease caused by Mycobacterium tuberculosis; these bacteria can live in the lungs and in various other organs of the body. This study aimed to determine what factors relate to adherence to pulmonary anti-tuberculosis drugs in patients with pulmonary tuberculosis at the Karya Mukti Public Health Center, Ogan Komering Ulu District in 2022. The quantitative research method used in this study was a cross sectional design. The population in this study was families with pulmonary TB patients in the work area of ??the Karya Mukti Health Center in 2022. The sampling method in this study used a total sampling technique. The number of samples in this study was 36 respondents. a questionnaire distributed to collect the data. From the results of statistical analysis by using the chi-square test, it shows that there was a significant relationship (p value < 0.05) for knowledge (p value 0.008), motivation (p value 0.019), and family support (p value 0.048). There was no relationship between age (p value 0.49), gender (p value 0.345) and the role of officers (p value 0.296). From the results of the multivariate analysis, it was found that the dominant factor on adherence to pulmonary OAT in patients with pulmonary tuberculosis at the Karya Mukti Health Center, Ogan Komering Ulu Regency in 2022, was knowledge (p value 0.011) (OR 6.87). From this research, it is hoped that the Health Center will provide counseling guidance to families, so that families can find out what can be done for families with pulmonary TB.